Trying to assess the quality of macroeconomic data: The case of Swiss labour productivity growth as an example - Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2007)
Macroeconomic data are indispensable for modern governance, yet it is often unclear how reliable these data are. The production process of macroeconomic data inside the statistical offices is often not very transparent for the general public. Bystanders usually have no choice but to take for granted the published data because criteria by which to judge data quality are wanting. Hoping to contribute to a better understanding of the quality of macroeconomic data, this paper proposes several plausibility checks and applies them to recently published Swiss labour productivity growth figures. Although the proposed checks cannot prove or disprove the official data, they are capable of either strengthening our confidence in the official data or, alternatively, of casting them into doubt. Policy debates drawing on official data will hardly be able to ignore differences in the degree of confidence with which these data are held to be accurate.
Keywords: C82; O47; 330; Accuracy of macroeconomic observations; statistical artefacts; labour productivity; Arbeitsproduktivität; Datenqualität; Statistischer Test; Schweiz